2007
DOI: 10.1542/peds.2006-3707
|View full text |Cite
|
Sign up to set email alerts
|

Preschooler Obesity and Parenting Styles of Mothers and Fathers: Australian National Population Study

Abstract: This article is the first, to our knowledge, to examine the parenting of both parents in relation to preschoolers' BMI status while also adjusting for parental BMI status. Fathers' but not mothers' parenting behaviors and styles were associated with increased risks of preschooler overweight and obesity. Longitudinal impacts of parenting on BMI gain remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
214
5
18

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(251 citation statements)
references
References 37 publications
14
214
5
18
Order By: Relevance
“…A weighted multinomial regression model (weighted by 2008 population weights as specified in the LSAC data set) was fitted to the data using 2008 child weight status as the outcome variable and 2004 maternal and paternal weight status as the predictor. We controlled for a number of parent and child covariates, as used in previous LSAC analyses 14 including child sex (male or female), English as main language spoken (yes or no), number of siblings at 4-year follow-up (none, 1, 2, or 3 or more) and child weight status as measured in 2004 (healthy, overweight, obese). Parent covariates included their education level at follow-up (less than 12 years, 12 years (that is, completed high school), or more than 12 years) and their weight status in 2008 (healthy, overweight, obese).…”
Section: Discussionmentioning
confidence: 99%
“…A weighted multinomial regression model (weighted by 2008 population weights as specified in the LSAC data set) was fitted to the data using 2008 child weight status as the outcome variable and 2004 maternal and paternal weight status as the predictor. We controlled for a number of parent and child covariates, as used in previous LSAC analyses 14 including child sex (male or female), English as main language spoken (yes or no), number of siblings at 4-year follow-up (none, 1, 2, or 3 or more) and child weight status as measured in 2004 (healthy, overweight, obese). Parent covariates included their education level at follow-up (less than 12 years, 12 years (that is, completed high school), or more than 12 years) and their weight status in 2008 (healthy, overweight, obese).…”
Section: Discussionmentioning
confidence: 99%
“…Three aspects of feeding previously associated with healthy child eating behavior and weight status were targeted: (1) increased exposure to healthy foods and decreased exposure to unhealthy foods to promote the development of healthy food preferences, [19][20][21][22]32 (2) responsive feeding that recognizes and responds appropriately to infant cues of hunger and satiety to promote self-regulation of intake, 15,16,18 and (3) positive parenting (warmth, encouragement of autonomy, and selfefficacy). [33][34][35] We used an anticipatory guidance framework to provide parents with information about behaviors to expect and constructive ways to manage these, rather than parents seeking advice on established problems. 36 The control group had self-directed access to universal community child health services, potentially child weighing, and information via the Internet or telephone help line.…”
Section: Interventionmentioning
confidence: 99%
“…Some studies have found effects on BMI of fathers' but not mothers' permissive and disengaged parenting styles (e.g., Wake, Nicholson, Hardy, & Smith, 2007) while other studies report no effects of either parents' parenting style on BMI (e.g., . Therefore, although both general parenting style and feeding-related style appear to be important, the nature of the underlying relationship between the two, and the effect on child adiposity, is less clear.…”
Section: Parenting Stylesmentioning
confidence: 99%